Gastin cells and fasting gastrin levels in duodenal ulcer patients: a quantitative study based on multiple biopsy specimens. Issue 2 (February 1979) - Piris, J; Whitehead, R
Abstract : The number of gastrin-producing cells in biopsy specimens from the gastric and duodenal mucosae in 19 duodenal ulcer patients was quantitated using a morphometric method. The level of immunoreactive gastrin in a sample of fasting serum obtained at the time of the biopsy was measured by radioimmunoassay. The results show no significant difference when compared with those from a group of normal control volunteers. Moreover, there was no correlation between the numbers of gastrin-producing cells and the fasting serum gastrin level in either controls or duodenal ulcer patients.